2017
DOI: 10.1634/theoncologist.2016-0479
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II, Randomized, Double-Blind, Placebo-Controlled Study of Simtuzumab in Combination with FOLFIRI for the Second-Line Treatment of Metastatic KRAS Mutant Colorectal Adenocarcinoma

Abstract: Lessons Learned. The safety profile in the patient groups who received FOLFIRI and simtuzumab did not differ from that in the FOLFIRI and placebo group.The addition of simtuzumab to chemotherapy with FOLFIRI does not improve clinical outcomes in patients with metastatic KRAS mutant colorectal carcinoma.Background.Simtuzumab, a humanized IgG4 monoclonal antibody to lysyl oxidase‐like 2 (LOXL2), blocks desmoplastic reaction in colorectal carcinoma (CRC) cells in vitro.Methods.Patients with metastatic Kirsten rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 14 publications
0
67
0
Order By: Relevance
“…Simtuzumab exhibited a good safety profile compared to the placebo group . However, despite greater supporting evidence in prior cellular studies in both the phase I & IIa clinical trials, Simtuzumab failed to show improved clinical outcomes when compared with the control arm .…”
Section: Is Loxl2 a Viable Cancer Target?mentioning
confidence: 82%
See 2 more Smart Citations
“…Simtuzumab exhibited a good safety profile compared to the placebo group . However, despite greater supporting evidence in prior cellular studies in both the phase I & IIa clinical trials, Simtuzumab failed to show improved clinical outcomes when compared with the control arm .…”
Section: Is Loxl2 a Viable Cancer Target?mentioning
confidence: 82%
“…Simtuzumab exhibited a good safety profile compared to the placebo group . However, despite greater supporting evidence in prior cellular studies in both the phase I & IIa clinical trials, Simtuzumab failed to show improved clinical outcomes when compared with the control arm . Cellular and human tissue studies conducted by Park showed a strong association between LOXL2 and metastatic potential, therefore it was surprising that the clinical trial showed no effect in this patient group.…”
Section: Is Loxl2 a Viable Cancer Target?mentioning
confidence: 92%
See 1 more Smart Citation
“…Latest clinical data might underline the necessity to conduct further studies. Recently, phase II trials combining treatment with a LOXL2-directed antibody (simtuzumab) with chemotherapygemcitabine in PDAC and FOLFIRI regiment in CRC-ended with unsatisfactory results Hecht et al, 2017). Drug scheduling in these trials were not designed to synergistically profit from improved drug delivery after ECM modification, but on the assumption of an additive effect of the cytotoxic drugs with the antitumoral effect that has been demonstrated preclinically for LOXL2 blockade by itself (Barry-Hamilton et al, 2010;Rodriguez et al, 2010).…”
Section: Targeting Collagen Synthesis and Maturationmentioning
confidence: 99%
“…), or in a phase II trial in metastatic KRAS mutant colorectal adenocarcinoma (Hecht et al . ). However, it should be pointed out here that in these trials, the late‐stage terminal nature of disease in these patients was unlikely to yield significant results, and as such, earlier treatment will likely lead to more promising results in line with preclinical studies using lysyl oxidase inhibitors in breast (Erler et al .…”
Section: The Therapeutic Repertoire Of the Matrix In Diseasementioning
confidence: 97%